Analysis of the genotype x environment interaction in Musa trials - Cauwer, I. de; Ortíz, R. (Cambridge University Press, 1998)
Plantain hybrids and landraces, and banana cultivars (Musa spp. L.) were evaluated for three years in the plant and ratoon crops at three locations in the humid lowland forest (Mbalmayo and Onne) and derived savanna (Ibadan) agro-ecozones of sub-Saharan Africa. Additive main effects and multiplicative interaction (AMMI) models accounted for a significant percentage of the genotype × environment interaction (GE) affecting bunch weight (kg plant−1) and yield potential (t ha−1 a−1). Obino l'Ewai, a plantain landrace, showed little GE for bunch weight, whereas the exotic cooking banana cultivar Cardaba had the most stable yield potential as revealed by the biplots of the GE analysis (AMMI-2 biplots). Plantain hybrids achieved high yield potential due to their short growth cycle. The high yield potential of the cooking bananas was mainly the result of their fast sucker development.